The Amino Acid Substitution Q65H in the 2C Protein of Swine Vesicular Disease Virus Confers Resistance to Golgi Disrupting Drugs - Vázquez-Calvo, Ángela; Caridi, Flavia; González-Magaldi, Mónica; Saiz, Juan-Carlos; Sobrino, Francisco; Martín-Acebes, Miguel A. (Frontiers in Microbiology, 2016)
Swine vesicular disease virus (SVDV) is a porcine pathogen and a member of the species Enterovirus B within the Picornaviridae family. Brefeldin A (BFA) is an inhibitor of guanine nucleotide exchange factors of Arf proteins that induces Golgi complex disassembly and alters the cellular secretory pathway. Since BFA has been shown to inhibit the RNA replication of different enteroviruses, including SVDV, we have analyzed the effect of BFA and of golgicide A (GCA), another Golgi disrupting drug, on SVDV multiplication. BFA and GCA similarly inhibited SVDV production. To investigate the molecular basis of the antiviral effect of BFA, SVDV mutants with increased resistance to BFA were isolated. A single amino acid substitution, Q65H, in the non-structural protein 2C was found to be responsible for increased resistance to BFA. These results provide new insight into the relationship of enteroviruses with the components of the secretory pathway and on the role of SVDV 2C protein in this process.